Sublingual microcirculation predicts survival after out‐of‐hospital cardiac arrest. (26th October 2021) - Voß, Fabian; Karbenn, Matthias; Hoffmann, Till; Schweitzer, Julian; Jung, Christian; Bernhard, Michael; Kienbaum, Peter; Kelm, Malte; Westenfeld, Ralf
Abstract: Background: Despite successful resuscitation with return of spontaneous circulation (ROSC), the prediction of survival in patients suffering out‐of‐hospital cardiac arrest (OHCA) remains difficult. Several studies have shown alterations in sublingual microcirculation in the critical ill. We hypothesized that early alterations in sublingual microcirculation may predict short‐term survival after OHCA. Methods: We prospectively included all adults admitted to our university hospital between April and September 2019 with ROSC following OHCA. Sidestream dark‐field microscopy to obtain sublingual microcirculation was performed at admission and after 6, 12 and 24 hours. Primary outcome was survival until discharge. Results: Twenty‐five patients were included. Six hours after ROSC, the proportion of perfused small vessels (PPVsmall ) was lower in non‐survivors than in survivors (85 ± 7.9 vs. 75 ± 6.6%; p  = .01). PPVsmall did not correlate with serum lactate. Stratification for survival with cutoff values >78.4% for PPVsmall 6 h post‐admission and <5.15 mmol/l for initial serum lactate as suggested by ROC‐Analyses results in a positive predictive value of 100% and a negative one of 67% for our study population. Conclusion: Estimating short‐term prognosis of OHCA patients with ROSC may be supported by measuring the PPVsmall at the sublingual microcirculation 6 hours after admission.